2006
DOI: 10.1086/508227
|View full text |Cite
|
Sign up to set email alerts
|

SpitzerSAGE Survey of the Large Magellanic Cloud. II. Evolved Stars and Infrared Color-Magnitude Diagrams

Abstract: Color-magnitude diagrams (CMDs) are presented for the Spitzer SAGE (Surveying the Agents of a Galaxy's Evolution) survey of the Large Magellanic Cloud (LMC). IRAC and MIPS 24 µm epoch one data are presented. These data represent the deepest, widest mid-infrared CMDs of their kind ever produced in the LMC. Combined with the 2MASS survey, the diagrams are used to delineate the evolved stellar populations in the Large Magellanic Cloud as well as Galactic foreground and extragalactic background populations. Some 3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
166
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 169 publications
(175 citation statements)
references
References 49 publications
3
166
1
Order By: Relevance
“…Vijh et al 2009;Boyer et al 2011) follow the scheme introduced by Blum et al (2006) to divide the found AGB objects into three distinct classes tagged "O-rich", "C-rich", and "Extreme". Recently, efforts were made to interpret the SEDs of these objects (defined by photometry compiled from various catalogues; cf.…”
Section: Extremely Reddened C Starsmentioning
confidence: 99%
“…Vijh et al 2009;Boyer et al 2011) follow the scheme introduced by Blum et al (2006) to divide the found AGB objects into three distinct classes tagged "O-rich", "C-rich", and "Extreme". Recently, efforts were made to interpret the SEDs of these objects (defined by photometry compiled from various catalogues; cf.…”
Section: Extremely Reddened C Starsmentioning
confidence: 99%
“…Only the subset of SAGE-Spec sources that had a full 5−37 μm spectrum are shown here. We refer the reader to Blum et al (2006) for a detailed description of the various stellar populations observed in these diagrams and to Paper IV for discussion on the locations of the oxygen-rich AGB candidates and models.…”
Section: Color-magnitude and Color-color Diagramsmentioning
confidence: 99%
“…4, is used in Blum et al (2006) and Paper I to select extreme AGB stars. It is somewhat similar to the K s vs. J − K s CMD.…”
Section: [36] Vs J − [36] Cmdmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a significant population of background galaxies, uniformly distributed over the SAGE-LMC footprint (Whitney et al 2008;Kozłowski & Kochanek 2009). The SAGE-Spec program (Kemper et al 2010) is a Spitzer spectroscopic follow-up survey designed to verify the initial SAGE-LMC classifications (Meixner et al 2006;Blum et al 2006;Whitney et al 2008) and investigate the nature of sources that could not be identified based on their photometry. Here we report on a point-source, in the SAGE-LMC catalogue 1 identified as SAGE1CJ053634.78-722658.5, (hereafter referred to as SAGE1CJ053634) at moderate redshift (z = 0.14) as derived from the observed wavelength of the polycyclic aromatic hydrocarbon (PAH) features, which is entirely dominated in its IR spectral energy distribution (SED) by warm dust (silicate) emission, rather than emission from star formation which is the case in nearly all other galaxies yet observed.…”
Section: Introductionmentioning
confidence: 99%